Burnout components, perceived stress and hair cortisol in healthcare professionals during the second wave of COVID 19 pandemic - Fortuna, Federico (2024)
This study evaluates the impact of the COVID-19 pandemic on healthcare workers in Argentina, duringthe second wave in 2021. The aim is to assess stress and burnout, incorporating the assessment of haircortisol levels as a biomarker of chronic stress. A total of 496 healthcare workers from three differenthospitals were included in this study. Two of these hospitals depend on the Buenos Aires City Ministryof Health and the third hospital belongs to Buenos Aires University. Hair samples were obtained usingscissors from the posterior vertex, as close to the scalp as possible. Each sample was weighed, andcortisol was extracted and then measured using an automated chemiluminescent method. Notably,10% of the population exhibited hair cortisol levels above 128 pg/mg. Associations were foundbetween high hair cortisol levels and age, workload, emotional exhaustion, and depersonalization.In addition, burnout, identified in 11% of participants, correlated with higher perceived stress andlower social support. Binary logistic regression revealed associations between burnout and perceivedstress, and age. Finally, mediation analysis showed depersonalization as a mediating variable inthe relationship between hair cortisol concentration and emotional exhaustion. In conclusion, thisstudy highlights the complex relationships between stress, cortisol levels, and burnout. Prioritizinginterventions and research is essential to support the well-being of frontline healthcare professionals,ensuring their resilience during challenging times.